COMMUNITY STRUCTURE AND TROPHIC STATUS OF REEF FISH IN NATUNA WATERS - Isa Nagib Edrus; Pratiwi Lestari (Indonesian Fisheries Research Journal, 2020)
A field research on reef fish-community structures in Natuna waters was carried out in November 2015. This research aimed to obtain the trophic composition of reef fishes and its correlation to diversity, density, and biomass. Underwater visual census on several transect areas was used to collect data. Results show that the identified reef fishes were about 100 species of target-reef fish belonging to 18 families and 23 species of indicator-reef fish of the Chaetodontidae family. The mean species number of target reef fish and indicator reef fish were 42 and 7 species, respectively. The  mean density of the target reef fish and indicator reef fish were 0.4 and 0.05 individual per m2, respectively. The mean of the reef fish relative stock was 0.6 ton/ha. The composition of the herbivores mostly found in the resilient coral reefs r was 46.45 % and the omnivores and planktivores as marketable targeted fishes were 18.64 % and 14.28 %, respectively. The most predominant or major families were from herbivorous, carnivorous, planktivorous, and corallivorous fishes, including Scaridae (i.e. Scarus spp), Lutjanidae (i.e. Lutjanus spp.), Caesionidae (i,e. Caesio cuning and Pterocaesio caerulaurea), and Chaetodontidae (i.e. Chaetodon baronessa and Chaetodon octofasciatus). The results suggested that the community structures were quite prospectively implemented for fisheries; however, it may not be promising for coral resilience. Furthermore, the coral health status was at moderate level in regard to the high numbers of corallivorous butterflyfishes.